The role of agricultural insurance: Gender and nutrition dimensions - Msangi, Siwa (International Food Policy Research Institute, 2017)
Smallholder farmers in Africa, Asia, and elsewhere are highly exposed to crises or “shocks” in both their physical and their socioeconomic environments. Like all households, smallholder farm households seek ways to reduce their exposure to these shocks and to find ways of smoothing their income streams and, hence, consumption levels to avoid volatile “feast and famine” cycles.